Types of Argumentation in Editorials - E. A. Nikonova (Научный диалог, 2024)
This article explores argumentation in the genre of editorials. The objective was to determine the frequency of different types of argumentation used in this genre, which can shed light on the balance between objective and subjective elements. It was found that editorials exhibit a balance between strong and weak argumentation, with 41% and 55.6% respectively (3.4% accounted for insufficient argumentation). The dominance of weak argumentation can be attributed to the specific nature of editorials, which aim to present the editorial board’s opinion and influence readers. The genre under study is a powerful tool in media warfare and shaping societal beliefs and values. The minimal percentage of insufficient argumentation indicates a desire to refrain from overt manipulation. The relatively high percentage of strong argumentation in a genre categorized as ‘opinion’ is also explained by the functional aspect of editorials: since the genre transmits institutional opinions with the intention of influencing public views, it is necessary to maintain authority and a high level of credibility in the information provided. Strong arguments in this genre include references to facts, data from authoritative sources including statistics, experimental results, references to public opinion, and common sense. Weak arguments include personal opinions, speculations, predictions, intuition, references to sources that are not definitive authorities in the field, conclusions based on incomplete statistical data and facts with no obvious connection.